Aktivitas antikanker senyawa bioaktif dari Paracaudina australis: Studi in silico yang menargetkan AKT1 dan NOS2 - Sukmiwati, Mery; Susilawati, Susilawati; Islami, Deri (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Sea cucumber isolates (Paracaudina australis) have shown potential as agents with various bioactivities. Bioactivity refers to the ability of a substance to interact with biological tissues and elicit positive physiological responses. This study aimed to analyze the interaction between the target proteins RAC-alpha serine/threonine-protein kinase (AKT1) and Nitric Oxide Synthase 2 (NOS2) with compounds identified in P. australis. The methods employed included ligand preparation using the Open Babel 2.3.1 plug-in, bioactivity prediction via the PASS Online web server, ADMET analysis using Canonical SMILES, pathway prediction using the DAVID (Database for Annotation, Visualization, and Integrated Discovery) web server, prediction of active or functional sites in proteins using BIOVIA Discovery Studio software, molecular docking using AutoDock Vina integrated in PyRx 0.8, visualization with BIOVIA Discovery Studio 2019, and molecular dynamics simulation using the WebGro web server. The results revealed that the P. australis sea cucumber isolate contained 38 compounds predicted to exhibit bioactivities related to the target proteins, including anticancer, anti-proliferative, pro-apoptotic, anti-inflammatory, anti-type 2 diabetes, and anti-obesity effects. Based on five ADMET parameters, all compounds satisfied several pharmacokinetic and toxicity criteria. Protein interaction analysis indicated that AKT1 and NOS2 interacted with other proteins, such as MTCP1, TCL1A, and NOX1. Molecular docking results showed that the compounds Ergosta-7,22-dien-3-ol, (3β,5α,22E); Ergostan-3-ol; Ergost-7-en-3-ol, (3β,5α); and Stigmasta-7,16-dien-3-ol, (3β,5α) exhibited the most stable binding to AKT1. Additionally, the compounds Ergosta-7,22-dien-3-ol, (3β,5α,22E) and Ergosta-7,22-dien-3-ol, (3β,22E) demonstrated lower binding affinity values than the control NOS2 inhibitor, indicating strong potential as NOS2 inhibitors.